EMERGENCY DEPARTMENT INTERVENTIONS FOR OLDER ADULTS: RESULTS OF A SYSTEMATIC REVIEW. (16th November 2018) - Hughes, J; Freiermuth, C; Ragsdale, L; Eucker, S; Shepherd-Banigan, M; Hastings, S; Gordon, A; Williams, J
Abstract: Older adults visit the Emergency Department (ED) at twice the rate of younger adults. A combination of demographic, clinical, and environmental factors can complicate the care older adults receive in the ED. These complications have well-documented associations with negative outcomes, including recurrent ED visits and hospitalization. This systematic review evaluated the effect of ED interventions on improving clinical and utilization outcomes. English-language studies published through 2017 which evaluated use of one or more eligible intervention strategies (discharge planning, case management, medication safety/medication management, and geriatric emergency departments) with older adults aged 65+ were included. Studies were categorized based on number of intervention strategies (single vs. multi-strategy) and key intervention components (assessment, referral plus follow-up, and planned contacts both before and after ED discharge). A total of 2, 000 articles were identified; 17 articles describing 15 unique studies (9 randomized; 6 non-randomized) met eligibility criteria. One-half of studies (n=7) evaluated multi-strategy interventions. Four studies included all three key intervention components. Quantitative and qualitative analyses indicated mixed effects of ED interventions on select outcomes. Multi-strategy interventions may be associated with a small effect on functional status, as indicated by less decline in functional independence. Single-contact interventions do not improve utilization outcomes. More comprehensive interventions, defined as presence of all three intervention components, may be associated with decreased hospitalization and ED readmission. There were no effects of ED interventions on mortality. Variability in study populations, intervention strategies, and intervention components make it difficult to draw conclusions about the effectiveness of any single intervention strategy.